Risk Assessment among Pregnant Women in Nigeria: Requisite Step towards Reduced Maternal Morbidity and Mortality - Afolabi, Adebukunola Olajumoke; ESIENUMOH, Ekpoanwan; Afolabi, Kolade Afolayan; Omishakin, Monisola Yetunde J.; Ayamolowo, Love B. (Universitas Andalas, 2023)
Existing risk assessment tools in pregnancy are limited in their predictive capabilities, whereas effective risk assessment should incorporate non-medical variables such as cultural and religious contexts of women, typical of African settings. This sstudy explored perception about risk in pregnancy, assessed knowledge about risk in pregnancy, examined risk status and related factors among pregnant women in Ile-Ife, southwest Nigeria. Study employed sequential explanatory mixed method design. Quantitative datac was collected using modified Dutta & Das Prenatal Scoring System from 239 pregnant women selected through a two-stage sampling technique. Regression analysis examined relationship between dependent and independent variables. Level of significance was p<0.05. Focus Group Discussion explored participants’ perception about risk in pregnancy. Qualitative responses were analyzed thematically. Findings showed that 80.5% had positive perception about risk in pregnancy, 19.5% had negative perception, 29.0% had good knowledge about risk in pregnancy, 17.3% of the pregnant women had poor knowledge while 53.7% had fair knowledge. Study observed significant relationship between high risk in pregnancy and age group 15-24 years (p=0.01, RRR= 0.67, CI= 0.12-3.63), ethnicity (p=0.02, RRR=12.93, CI=1.42-117.76), poor knowledge about risk in pregnancy (p=0.03, RRR=4.08, CI=1.19-13.98), primigravidity (p=0.001, RRR=0.01, CI=0.002-0.08), multigravidity (p=0.001, RRR=0.04, CI=0.02-0.29) and vaginal birth (p=0.001, RRR=0.21, CI= 0.08-0.54). Qualitative findings resulted in three themes namely; women’s perception about risk in pregnancy, perceived causes of risk in pregnancy, perceived risk preventive measures in pregnancy. Study concluded that women’s age, ethnicity, knowledge about risk in pregnancy, gravidity and mode of birth were main predictors of risk in pregnancy. Intervention programs should take cognizance of these variables especially cultural contexts of women.